Pickles: Independent Biology Practicum Diffusion and Material Osmosis On the Concept of Substance Transport during the Pandemic Period - Nawawi Nawawi; Isra 'Indar Handayani; Sukardi Sukardi (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2021)
Teachers had difficulty developing Science Process Skills in biology subjects during the Pandemic at SMA Negeri 1 Sambit Ponorogo. This study aims to 1) analyze the Science Process Skills of class XI IPS 1 student at SMA Negeri 1 Sambit Ponorogo in Biology learning through pickle making practicum, 2) describe the involvement of parents in biology learning during distance learning. The research design used One-Shot Case Study. The research subjects were 27 people from class XI IPS 1 SMA Negeri 1 Sambit Ponorogo. The research instrument used a Science Process Skills observation sheet, an independent practicum assessment sheet, and an online questionnaire for parents & students. The analysis was carried out by descriptive quantitative. Based on the implementation results, it is known that Science Process Skills are categorized as good in independent practicum activities, where the ability to apply is 89.91%, concludes 78.70%, proposes 90.74% hypotheses, predicts 77.78%, and observes 92.59%. While 62.59% of parents are less involved in helping students while learning from home, this affects the success of distance learning. The conclusion of this research is; 1) Practicum making events can be used in applying Science Process skills of Class XI IPS 1 student at SMA Negeri 1 Sambit Ponorogo, 2) Parental involvement in biology learning during distance learning in Class XI IPS 1 SMA Negeri 1 Sambit Ponorogo needs to be improved, because of involvement parents are still very low during distance learning in class XI IPS 1 SMA Negeri 1 Sambit Ponorogo.